Penerapan Model Creative Problem Solving berbasis STEAM untuk Meningkatkan Keterampilan Pemecahan Masalah Siswa - Maflahah, Chadhirotul; Purnomo, Aris Rudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This studi aims to analyze the improvement in students’ problem-solving skills through a STEAM-based creative problem-solving learning model in science education at the junior high school level. The type of research used is quantitative descriptive, employing a one-group pretest-posttest design involving 28 ninth-grade students from Class IX B at SMP Negeri 11 Gresik. The research results were obtained from the students’ pretest-posttest answer sheets in the learning process, which consisted of 8 essay questions. This study shows that students' problem-solving skills improved, with an N-Gain score of 0.6 (moderate category) and a Wilcoxon test with a significance level of <0.001. This indicates that the STEAM-based creative problem-solving learning model can enhance the problem-solving skills of junior high school students.